Use of systemic low-dose unfractionated heparin in microvascular head and neck reconstruction: Influence in free-flap outcomes. Issue 3 (3rd May 2016) - Numajiri, Toshiaki; Sowa, Yoshihiro; Nishino, Kenichi; Arai, Akihito; Tsujikawa, Takahiro; Ikebuchi, Kaichiro; Nakano, Hiroshi; Sakaguchi, Hirofumi
Abstract: Background : Intravenous heparin administration is used to prevent thrombosis in free-flap transfer. However, it is unknown whether the use of heparin affects free-flap survival. The purpose of this study is to investigate the effect of heparin in free flap transfer. Methods : Two hundred and six patients who received ablative surgery for head and neck cancer were classified into three groups. Group A received ablative surgery, neck dissection, and free-flap reconstruction, and postoperatively they were administered continuous intravenous unfractionated heparin (5000–10 000 units/day) until postoperative day 7 (POD7); group B received the same procedures as group A but without heparin; group C received only ablative surgery and neck dissection without heparin. As indicators of coagulation time, the prothrombin time-international normalised ratio (PT-INR) and the activated partial thromboplastin time (APTT) were measured, before surgery and on POD1, 3, and 7. Flap failure, bleeding, haematoma formation, re-exploration, and thromboembolic events were recorded. Results : The PT-INR and APTT were 1.3–1.5-times longer in group A ( p < 0.01), and 1.3-times longer ( p < 0.01) in group B. The PT-INR and APTT were higher in groups A and B than C ( p < 0.01). The free-flap success rate was not affected. Only the incidence of haematoma was increased in group A ( p = 0.04). Conclusion : Heparin increased the haematoma formation, but did not change the incidence of free-flap failure. Thus, the intravenous low-dose heparin use does not affect microvascular flap survival.